Rwanda - Agricultural and Rural Market Development - Mohan, P. C. (World Bank, Washington, DC, 2012)
This Credit of US$5 million was a Learning and Innovation Loan ( LIL ) -- implemented 1999-2003 -- whose objective was to contribute to revitalizing the country's agricultural and rural economy by identifying policies and institutional mechanisms to promote efficient, private sector-based local agricultural input distribution and out put marketing systems in order to raise modern farm input use among farmers and thereby the productivity of labor and levels of income in the rural sector. The project was implemented in 20 districts, representing about 25 percent of the total number of districts. It affected 21,00 farm families, with a population of 1.05 million, including about 1,000 lead farmers and 1,000 Farmers'Associations.